Does revolution change risk attitudes? Evidence from Burkina Faso - Mohammad H. Sepahvand; Roujman Shahbazian; Ranjula Bali Swain (Uppsala University, Department of Economics, 2019)
A popular uprising in 2014, led to a revolution overthrowing the sitting president of Burkina Faso. We investigate if individuals' risk attitudes changed due to this revolution. Specifically, we investigate the impact of the revolution on risk attitudes, by gender, age and level of education. The analysis is based on a unique nationally representative panel Household Budget Survey, which allows us to track the changes in the risk attitudes of the same individuals before, during and after the revolution. Our results suggest that the impact of the revolution is short-term. Individuals become risk averse during the revolution but converge back to the pre-revolution risk attitudes, slightly increasing their risk taking, after the revolution is over. Women are more risk taking than the men after the revolution but are more risk averse during the revolution. In general, older individuals tend to have higher risk aversion than the younger individuals. During the revolution, however, the individuals with higher level of education are less willing to take risk.
urn:nbn:se:uu:diva-376700
Keywords: D12; D74; D81; O12; Z10; 330; exogenous shock; revolution; gender; Burkina Faso